Plant extracts: Nanoparticle sources - Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan; Mashitah, Mohd Yusoff (Elsevier, 2020)
Nanoparticles (NPs) (usually in dimensions of 1–100 nm) have been proven, throughnumerous research findings, to have excellent properties in term of physiochemical, anti-fungal, chemical, catalytic, thermal conduction, mechanical, electrical, optical, and manymore. NPs have vital roles in agro-production and protecting crops from diseases,both directly and indirectly, and they go even further to influence the soil microbialpopulation. At the nanoscale, the elementary understanding of chemical and physicalproperties is very distinctive. As such, research outputs at different scales will have dif-ferent interpretations that in turn radiate different properties, even for the same element.Owing to the superior qualities of NPs, research on them is intense, as many researchersare intensively working in the area. Nanoparticle utilization is glaring in many areas,including healthcare and cosmetics, food and feed, drug delivery systems, the space indus-try, electronics, optoelectronics, biomedical science, and man